Revealed demand for country-of-origin labeling of meat in the United States - Taylor, Mykel R.; Tonsor, Glynn T. (My University, 2013)
Proponents of the U.S. mandatory country-of-origin labeling (MCOOL) law have argued that consumers prefer domestic meat and value labels confirming domestic origin. Following legislation enacted in March 2009, an ex post analysis of demand is possible to evaluate relative costs and benefits of MCOOL. This study uses retail grocery-store scanner data to estimate a Rotterdam demand model of meat products. The model results failed to detect changes in consumer meat demand post-MCOOL. Given the costs of compliance incurred by meat processors and no evidence of increased demand, our results suggest that producers and consumers have experienced a welfare loss.
Keywords: Country of origin; MCOOL; Meat demand; Rotterdam; Separability